Improving the Effectiveness of Education through the Use of Modern Information and Communication Technologies in the Training of Designers - Muslimov Narzulla Alekhanovich; Umarova Fotima Abdurakhimovna (Newinera Publisher, 2020)
The article describes the pedagogical conditions for organizing the educational process, training designers using modern information and communication technologies, performing tasks for students in practical and laboratory classes. The radical solution to the problem of increasing the effectiveness of education is not to expand the technical capabilities of modern information technology, but to develop a system of didactic and methodological principles of their application in the educational process.